State Languages for Second and Foreign Speakers: teaching and learning Croatian and Macedonian at university level - Jelaska, Zrinka (Array, 2008)
This paper analyses sociolinguistic status of two languages as second and foreign at the university level: Croatian and Macedionian. Both are state and official languages which are acquired and/or learned by minority speakers within the country, as well as foreigners within or outside the country. There are also some heritage speakers, with a certain degree of communicative competence, who get enrolled at university courses to improve their knowledge. The analysis of teaching and learning state languages as L2 in two plurilingual Slavic countries: Croatia and Macedonia will reveal some of various factors that may influence L2 development. Some concern minority languages, esp. Albanian, Serbian and Roma in both countries, Italian, Hungarian and Czech in Croatia, and Turkish in Macedonia. The sociolinguistic status of minority languages within the country is analyzed, as well as social status of its speakers, their motivation and educational needs. Some concern heritage speakers and their motivation, and some foreign, non-heritage state language learners and their motivation. The similarities and differences will be presented, esp. between geo-political position of both countries.